2009
DOI: 10.1266/ggs.84.209
|View full text |Cite
|
Sign up to set email alerts
|

A dominant mutation of TWISTED DWARF 1 encoding an .ALPHA.-tubulin protein causes severe dwarfism and right helical growth in rice

Abstract: Dwarfism is a common type of mutation in many plant species. The pathways and factors regulating biosynthesis and signaling of several plant growth regulators have been clarified through analyses of dwarf mutants in rice, Arabidopsis, pea, and maize. However, the genetic mechanisms controlling dwarfism are not well characterized, and the causal genes underlying most dwarf mutants are still uncovered. Here, we report a dominant mutant, Twisted dwarf 1-1 (Tid1-1), showing dwarfism and twisted growth in rice. Tid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 45 publications
2
44
0
1
Order By: Relevance
“…Although cellulose-deficient mutants (i.e., mutants that have reduced CESA velocities and cellulose content) typically display defects in microtubule organization (Paredez et al, 2008), no spiraling phenotypes have been reported. Moreover, clasp and other microtubule-related mutants also affect mitotic activity, presumably by disturbances in the mitotic spindle formation (Ambrose et al, 2007;Kirik et al, 2007;Sunohara et al, 2009). Interestingly, pom2/csi1 mutants also held a reduced number of cells that actively divided in the root meristem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cellulose-deficient mutants (i.e., mutants that have reduced CESA velocities and cellulose content) typically display defects in microtubule organization (Paredez et al, 2008), no spiraling phenotypes have been reported. Moreover, clasp and other microtubule-related mutants also affect mitotic activity, presumably by disturbances in the mitotic spindle formation (Ambrose et al, 2007;Kirik et al, 2007;Sunohara et al, 2009). Interestingly, pom2/csi1 mutants also held a reduced number of cells that actively divided in the root meristem.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from altered microtubule organization, mutations in several microtubule-associated genes also lead to reduced mitotic activity (Ambrose et al, 2007;Kirik et al, 2007;Sunohara et al, 2009). To test whether the pom2 mutants also hold fewer cells that actively divide, we crossed lines expressing the mitotic marker cycB1;1:Cyclin Destruction Box (CDB):b-glucuronidase (GUS) (Hauser and Bauer, 2000) with several pom2 mutant alleles.…”
Section: Pom2/csi1 Mutants Display Microtubule-related Phenotypes Andmentioning
confidence: 99%
“…In response to environmental and developmental stimuli, the microtubule system can be reoriented, such as undergoing clockwise or counterclockwise rotation in plant cells (Lloyd and Chan, 2004;Chan et al, 2007). In plants, components of the microtubule system have been shown to be critical for plant architecture (Thitamadee et al, 2002;Twell et al, 2002;Nakajima et al, 2004;Sedbrook, 2004;Sunohara et al, 2009). For example, the rice TWISTED DWARF1 (TID1) gene encodes an a-tubulin that influences plant morphology; a dominant mutation of TID1 caused disrupted cellular microtubule arrays, severe dwarfism, and right helical growth (Sunohara et al, 2009).…”
Section: Fh5 Affects the Formation Of Microtubule Arrays In Ricementioning
confidence: 99%
“…The gene for the semi-dominant, gain-of-function mutant Slr-d , located on chromosome 3, is a consequence of a mutation in the gene encoding the rice DELLA protein SLR1 , which functions as a repressor of GA signaling through an interaction with the GA receptor GID1 [7]. The gene for another dominant dwarf mutant, Twisted dwarf 1 ( Td1 ), was located on chromosome 11 and was found to encode the α-tubulin protein; this has been recognized as an additional factor that determines plant height through the regulation of microtubule formation [16]. The loci for other dominant dwarf mutants, including D53 , Ssi1 , Sdd(t) , Dx , and LB4D , were identified on chromosomes 11, 1, 6, 8, and 11, respectively [13][15], [17], [18].…”
Section: Discussionmentioning
confidence: 99%